Procedure for Destruction of Evidence of the Crime of Narcotics Abuse Based on Formal Law in Indonesia - Erwin Asmadi (International Journal Reglement & Society (IJRS), 2020)
Extermination of narcotics evidence is further regulated in Government Regulation of the Republic of Indonesia Number 40 of 2013 concerning Implementation of Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics, namely as a form of procedure for destroying narcotic evidence which is destroyed according to its type. Regulation of the Head of the National Narcotics Agency of the Republic of Indonesia Number 7 of 2010 concerning Technical Guidelines for Handling Confiscated Narcotics, Narcotics and Other Chemical Substances Safely, explains that the destruction of narcotics evidence, including marijuana is destroyed through the steps that have been set out therein. This regulation becomes a standard rule that must be implemented by the parties carrying out the destruction of confiscated evidence. This research is a type of normative legal research by means of literature study where the data is sourced from secondary data in the form of primary and secondary legal materials. Based on the results of the study, it is known that based on the hierarchy of regulations the procedures for destroying narcotics evidence are based on Article 91 and Article 92 of Law Number 35 of 2009 concerning Narcotics. Destruction of narcotic evidence is carried out before a court decision is made based on the determination of the local District Attorney's office and destruction after a court decision is based on an order of a judge's decision. Regarding the technical guidelines for destruction, the hierarchical stages of the destruction procedure are regulated in the Regulation of the Head of the National Narcotics Agency of the Republic of Indonesia Number 7 of 2010 concerning Technical Guidelines for Handling and Destruction of Confiscated Narcotics, Narcotics Precursors and Other Chemicals Safely